NUMERICAL METHODS USING CASIO FX-570ES CALCULATOR - Tay Kim Gaik; Lim Kian Boon; Rosmila Abdul Kahar (Penerbit UTHM, 2011)
This book is written for engineering students who take Numerical Methods at an undergraduate level. This book is published to accompany students who owned Casio FX-570ES instead of Casio FX-570MS calculator. The special about Casio FX-570ES calculator is that it is more users friendly and the display is more natural although it can only handle 7 variables (A, B, C, D, X, Y, M) if compared to Casio FX-570MS calculator can store 9 variables (A,B, C, D, E, F, X, Y, M). In this book, the image of keystroke answers is presented exactly as displayed on the screen of the calculator. Students need to get familiar and be comfortable with some basic keystrokes of Casio FX-570ES calculator and then proceed to the next chapters to maximize their capability in handling their calculator. We hope that this book is beneficial to the lecturers and students in teaching and learning environment.